EAD E A IMPORTÂNCIA DA AFETIVIDADE NO PROCESSO DE APRENDIZAGEM - Santana, Maria da Conceição Beltrão de; Cardoso, Luís Miguel Oliveira de Barros (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
This article explores the growing relevance of distance education and its impact on learning. The importance of affectivity in the remote educational context is highlighted, demonstrating how affective relationships between teachers and students play a fundamental role in engagement and academic success. The need to consider the affective dimension as a critical component of distance education is highlighted here, aiming to improve the quality of students' educational experience and the achievement of the best learning results.